Pregnancy complications and adverse birth outcomes among women with celiac disease: a population-based study from England - Abdul Sultan, Alyshah; Tata, Laila J.; Fleming, Kate M.; Crooks, Colin J.; Ludvigsson, Jonas F; Dhalwani, Nafeesa N.; Ban, Lu; West, Joe (Nature Publishing Group, 2014)
OBJECTIVES: Evidence-based information about adverse birth outcomes and pregnancy complications is crucial when counseling women with celiac disease (CD); however, limited population-based data on such risks exist. We estimated these for pregnant women with CD diagnosed before and after delivery. METHODS: We included all singleton pregnancies between 1997 and 2012 using linked primary care data from the Clinical Practice Research Datalink and secondary care Hospital Episode Statistics data. Risks of pregnancy complications (antepartum and postpartum hemorrhage, pre-eclampsia, and mode of delivery) and adverse birth outcomes (preterm birth, stillbirth, and low birth weight) were compared between pregnancies of women with and without CD using logistic/multinomial regression. Risks were stratified on the basis of whether women were diagnosed or yet undiagnosed before delivery. RESULTS: Of 363,930 pregnancies resulting in a live birth or stillbirth, 892 (0.25%) were among women with CD. Diagnosed CD was not associated with an increased risk of pregnancy complications or adverse birth outcomes compared with women without CD. However, the risk of postpartum hemorrhage and assisted delivery was slightly higher among pregnant women with diagnosed CD (adjusted odds ratio (aOR)=1.34). We found no increased risk of any pregnancy complication among those with undiagnosed CD. We only observed a 1% absolute excess risk of preterm birth and low birth weight among undiagnosed CD mothers corresponding to aOR=1.24 (95% confidence interval (CI)=0.82–1.87) and aOR=1.36 (95% CI=0.83–2.24), respectively. CONCLUSIONS: Whether diagnosed or undiagnosed during pregnancy, CD is not associated with a major increased risk of pregnancy complications and adverse birth outcomes. These findings are reassuring to both women and clinicians.